LITERATURE STUDY: IMPLEMENTATION OF PERFORMANCE-BASED BUDGETING IN REGIONAL FINANCIAL MANAGEMENT - Helia Khairani (Kajian Akuntansi, 2025)
This research was conducted to analyze the application of performance-based budgeting in financial management in various regions with certain policies and methods. The literature study in this research aims to review various related studies especially in the context of planning, budgeting, and evaluation that can achieve performance in local financial management. This includes evaluations in several local governments such as Lampung, Padang, Aceh, and Bengkalis. Although the results of this study show that the various initiatives undertaken have successfully achieved their objectives, each region faces various challenges such as less mature planning to be prepared, mismatches between budget realization and targets, as well as cultural and structural barriers within local government institutions. It can be concluded that the implementation of performance-based budgeting is an important step to improve effectiveness, efficiency and accountability in local financial management. The literature study in this research provides a contributory overview of various practices and challenges in various regions, and provides recommendations on how to improve financial accountability and budgeting efficiency. Thus, continuous improvement in planning, implementation, and monitoring is needed to address solutions to the challenges and achieve performance-based budgeting that can support better public service outcomes.